SPECIAL ROBOTS FOR ENERGETICS - Sit M.L.; Shkolnik Sofia; Andreev E.S.; Karpov E.; Chisteakov М. (Problems of the Regional Energetics)
An overview of robots used in the power industry for diagnostics of power lines, cable lines, for the control, monitoring and maintenance of wind turbines, in nuclear energy, for optimum orientation of solar photovoltaic plants and solar panels for cleaning. Equations of statics and dynamics of robotic car which lifts along the vertical flexible rope are considered. It is presented the design which is made on the basis of "Lego Mindstorms" to solve the problem.